Do Younger Entrepreneurs Perform Better in the Bengaluru Startup Ecosystem? - Sakthivel, Adithya Vikram (AMC Indian Journal of Entrepreneurship, 2021)
A common misconception prevalent in today’s world is the belief that young entrepreneurs are considerably more successful than their older counterparts. This paper quantitatively analyses 20 unicorn startups (a valuation exceeding 1 billion) exclusively coming out of Bengaluru, the Silicon Valley of India between the years 2011 and 2021, and the 35 or so entrepreneurs associated with them disproving this above-mentioned false statement in the process (given that unicorns could be considered the textbook definition of a successful startup). Additionally, this paper infers that there is no correlation between age of the entrepreneur(s) and time taken for a company to achieve unicorn status.